2010
DOI: 10.5694/j.1326-5377.2010.tb03561.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication when seeking informed consent: a randomised controlled study of a computer‐based method for providing information to prospective clinical trial participants

Abstract: Objective: To assess the efficacy, with respect to participant understanding of information, of a computer‐based approach to communication about complex, technical issues that commonly arise when seeking informed consent for clinical research trials. Design, setting and participants: An open, randomised controlled study of 60 patients with diabetes mellitus, aged 27–70 years, recruited between August 2006 and October 2007 from the Department of Diabetes and Endocrinology at the Alfred Hospital and Baker IDI He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Data regarding rates of participant satisfaction were tracked for eleven interventions. Preferences between interventions and controls were either insignificant or showed that participants significantly preferred the interventions [19,27,29,32,35,43,47,52-54]. Accrual rates, tracked for trials with real parent studies, were also reported as improved or unchanged by interventions in all categories [13,23,29,43,52,55,56], with one exception [46].…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding rates of participant satisfaction were tracked for eleven interventions. Preferences between interventions and controls were either insignificant or showed that participants significantly preferred the interventions [19,27,29,32,35,43,47,52-54]. Accrual rates, tracked for trials with real parent studies, were also reported as improved or unchanged by interventions in all categories [13,23,29,43,52,55,56], with one exception [46].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no clear standard for how much of an improvement in understanding is needed to justify the cost of developing a multimedia aid, and reviews of the literature have shown these efforts to have mixed results. 1819 In some studies, multimedia aids have improved participant understanding, 2021 while others have shown no significant improvement in knowledge despite participants’ reports that they found them worthwhile. 22 None of these studies have addressed understanding of research on medical practices specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies included limiting animation length, focusing on a relevant and practical topic, using simple and familiar language, visually reinforcing content, and using active voice with conversational style. 11,12 Animation-based education is quickly gaining an evidence base and offers great opportunity to overcome literacy barriers 13 by visually underscoring the message and improving comprehension, 10,14 recall, 14,15 and satisfaction with information delivery. 14,[16][17][18] In this paper, we review the patient-engaged development process for the animation and report preliminary evidence of its feasibility and acceptability from pilot testing the animation with kidney transplant candidates.…”
mentioning
confidence: 99%